Association of uric acid levels with the development of metabolic dysfunction-associated and metabolic and alcohol-related/associated steatotic liver disease: a study on Japanese participants undergoing health checkups - Tatsuya Fukuda; Taro Akihisa; Takahiro Okamoto; Takahiro Fukaishi; Akio Kawakami; Makoto Tanaka; Tetsuya Yamada; Koshiro Monzen (Endocrine Journal)
Hyperuricemia reflects increased insulin resistance, and uric acid (UA) may serve as a predictive marker for the development of metabolic dysfunction-associated steatotic liver disease (MASLD); however, few studies have investigated this condition in the Japanese population. Thus, this retrospective observational study aimed to investigate the association of hyperuricemia with the risk of MASLD or metabolic and alcohol-related liver disease (MetALD) in individuals undergoing health checkups. A cross-sectional analysis was performed on 58,110 individuals, dividing them into quartile groups according to UA values for men and women (Q1 being the lowest and Q4 being the highest), and examining the complication rate of MASLD/MetALD. Subsequently, among 22,364 individuals without MASLD/MetALD, the relationship between UA at baseline and MASLD/MetALD development during follow-up was investigated using Cox proportional hazard models. In the cross-sectional analysis, the higher UA group had a higher complication rate of MASLD/MetALD in both men and women. In the follow-up analysis, both genders in the higher UA quartiles had a significantly higher incidence of MASLD/MetALD than those in the lower quartiles. Multivariate Cox proportional hazards analysis revealed that Q4 had a significantly higher hazard ratio than Q1 for both genders. These trends were the same in the time-dependent body mass index (BMI) model, which incorporated BMI as a time-dependent variable. High UA levels may serve as a predictive marker for MASLD/MetALD development. UA monitoring during health checkups could enable early detection and provision of intervention, improving patient outcomes.